Disturbo dello Spettro Autistico e Aderenza al Trattamento - 1 Patrizia Marone, 1 Floriana Longobardi (Marp Edizioni, 2020)
Autism Spectrum Disorder and Treatment Adherence The work aims to highlight the results of the international scientific literature on the topic "Adherence to ABA treatment in the parents of people with Autism Spectrum Disorder". Interesting aspects emerge regarding the choice of treatment delivery modalities such as, for example, greater adherence by parents to use reinforcement rather than punishment in cognitive behavioral treatment (Moore, TR, & Symons, FJ, 2009). The literature highlights a poor knowledge of the contingencies that reinforce adherence to ABA treatment and / or adherence to other treatments by parents and, moreover, only some studies (Hayward, Fava, Kaiser & Roberts, 2013) include the coding on adherence to treatment by parents. Some authors have also highlighted a correlation (Casenhiser et al, 2013; Strauss et al, 2012) between changing parents' behavior and changing children's behavior.